Gewalt im Computerspiel Facetten eines Vergnügens - Bareither, Christoph (Kultur und soziale Praxis, 2017)
Grand Theft Auto, Battlefield, Counterstrike - more and more, violence in computer games is becoming the subject of heated discussion. But what emotional experiences does the playful use of virtual violence make possible? Through participato observation in online games and at LAN parties and analyses of interviews, magazines, and videos, Christopher Bareither presents in detail how millions of people can take pleasure from that which would shock others. By refraining from judgmental cliches, this ethnographic study is able to provide a decisive contribution to a debate at the crossroads of popular culture, politics, and the public sphere.